2019
DOI: 10.1038/s41393-019-0253-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of estimated energy requirements using predictive equations with total energy expenditure measured by the doubly labelled water method in acute spinal cord injury

Abstract: Study design Prospective, observational Objectives To evaluate agreement between a reference method (doubly labelled water, DLW) of total energy expenditure (TEE) and published equations for estimating energy requirements in acute spinal cord injury (SCI). Setting Victoria, Australia Methods Twenty participants (18 male) within 8 weeks of traumatic SCI completed DLW, anthropometric and dietary intake assessments. Energy requirements were predicted using Harris-Benedict, Schofield, Henry, Nelson, Buchholz and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…They are not radioactive, and can be administered in small amounts in their role in nutritional research. They have long been a safe tool for assessing various aspects of human nutrition, and continue to be so, often in potentially vulnerable groups including, for example, premature infants, children in both health and disease and individuals with severe injuries [2][3][4][5]. Whilst, as previously stated, radioactivity is not an issue with these two isotopes, it is right and proper that other aspects of the safety of these stable isotopes be considered and understood prior to their use in human studies.…”
mentioning
confidence: 99%
“…They are not radioactive, and can be administered in small amounts in their role in nutritional research. They have long been a safe tool for assessing various aspects of human nutrition, and continue to be so, often in potentially vulnerable groups including, for example, premature infants, children in both health and disease and individuals with severe injuries [2][3][4][5]. Whilst, as previously stated, radioactivity is not an issue with these two isotopes, it is right and proper that other aspects of the safety of these stable isotopes be considered and understood prior to their use in human studies.…”
mentioning
confidence: 99%
“…A recent study by Desneves and colleagues utilized the doubly labeled water technique to evaluate the validity of several predictive equations in a sample of 20 patients. Doubly labeled water studies were completed a median of 41 days (IQR, 28–48 days) post injury, and the authors determined that predictive equations that incorporated fat‐free mass into the calculations were more reliable than the others tested 25 . However, body composition testing is not currently completed during acute management of patients with acute, traumatic spinal cord injuries.…”
Section: Discussionmentioning
confidence: 99%
“…(90,94,95,98,102,103,130) In chronic SCI, TDEE is from 1332 to 2834 kcal/day (Table 4). (9,34,95,(99)(100)(101)122,131) TDEE is reduced in persons with chronic SCI by as much as 54% in persons with tetraplegia (131) and nearly 20% in individuals with paraplegia. (122) TDEE can be assessed by measuring average daily energy expenditure using direct, or whole body, calorimetry, doubly labeled water, and mechanical ventilation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(132) Thus, making the technique mathematically complex and prone to miscalculation. Double labeled water is infrequently used (Desneves et al (95) and Tanhoffer et al (100,101) ) to measure TDEE after SCI. In 2012 and 2015, Tanhoffer et al (100,101) reported a mean TDEE of 2346 and 2406 kcal/day, respectively, in chronic SCI, while Desneves et al (95) reported 2354 kcal/day during the acute stage.…”
Section: Accepted Manuscriptmentioning
confidence: 99%